Predictors of olfactory improvement after endoscopic sinus surgery in chronic rhinosinusitis with nasal polyps - Hernandez, A. K.; Wendler, Olaf; Mayr, Susanne; Iro, Heinrich; Hummel, T.; Müller, Sarina Katrin (Journal of Laryngology and Otology, 2022)
Objective. This study aimed to determine the predictors of olfactory improvement after endoscopic sinus surgery among patients with chronic rhinosinusitis with nasal polyps.
CRIS-Team WoS Importer:2023-04-21